Patients with pemphigus vulgaris under pathology and on the background of prolonged use of high doses of glucocorticosteroid therapy – the possibility of influencing the glutathione system - Litvinov, V. A.; Makurina, H. I.; Літвінов, Володимир Анатолійович; Макуріна, Галина Іванівна (My University, 2020)
The aim of the study was to increase the effectiveness of treatment of patients with PV with the substantiation and development of modern methods of corrective therapy based on the study of indicators of changes in the balance of the thiol-disulfide system in the body of patients under pathological conditions and with prolonged use of high doses of glucocorticosteroid hormones (GCS). Materials and research methods. There were examined 30 patients with PV (4 men and 26 women), who were hospitalized in KU «Zaporizhzhya Regional Skin and Venereal Clinical Dispensary» ZOR, Zaporizhzhia. At the time of observation, most of the patients were aged 61-70 years. As a comparison group, 20 practically healthy people were examined, constituting a control group.
Keywords: pemphigus vulgaris; glucocorticosteroids; glutathione reductase; glutathione peroxidase; thiols